Impact of Product Innovation and Technological Innovation on Organisational Performance: Evidence from Nigerian Money Deposit Banks - Badiru, Nafiu (Journal of Technology Management and Business, 2024)
The Impact of product and technological innovation on organisational performance in Osun State Deposit Money Banks was examined. The study population comprises 1356 staff of selected money deposit banks, of whom 331 were sampled. A survey research design approach was used, and questionnaires were used to gather the data analysed, with the use of descriptive and regression statistics method of data analysis. Findings revealed that product innovation significantly affected organisational performance (R2 = 0.243, Adjusted R2 = 0.236, p < 0.05). Further, technological innovation significantly influenced organisational performance (R2 = 0.434, Adjusted R2 = 0.429, p < 0.05). This study concluded that product and technological innovation significantly enhanced the organisational performance of money deposit banks in Osun State. Based on this conclusion, the study recommended that banks prioritise new product development and improve existing products. Also, banks should prioritise investments in technology and digital transformation to enhances their performance.